Model Predictive Circulating Current Control for the Hexverter - Uriarte-Gonzalez, M (Institute of Electrical and Electronics Engineers Inc., 2024)
Modular multilevel converters are a family of converters proposed for high-voltage and high-power applications. The hexverter topology was introduced as a direct AC-to-AC converter with a reduced number of clusters compared to other multilevel topologies. The control of the hexverter is complex and requires several stages. One of these stages, the balancing of the floating capacitor voltages, necessitates precise regulation of the converter s circulating currents. In this paper, a model predictive control strategy is proposed to regulate the circulating current of the hexverter. Simulation results demonstrate the effective performance of the proposed controller. © 2024 IEEE.